Epidemiology of lung cancer and lung cancer screening programs in China and the United States. (1st January 2020) - Yang, Dawei; Liu, Yang; Bai, Chunxue; Wang, Xiandong; Powell, Charles A.
Abstract: Lung cancer is a heterogeneous disease that is impacted by environmental exposures and by constitutional genetic or epigenetic susceptibilities to disease development and progression. The United States and China have distinct and diverse populations and geographic environmental exposures that contribute to unique patterns of lung cancer incidence and mortality. In this paper, the authors compare trends of incidence and mortality of lung cancer in the US and China, and the impact on lung cancer screening programs in the two countries. It is worth noting that the mortality of lung cancer in the US has decreased gradually while in China it is still increasing over recent years. While decreasing smoking prevalence and the impact of clean air legislation have helped to mitigate the trend in the US relative to China, the increasingly widespread implementation of lung cancer chest CT screening is expected to impact lung cancer incidence and mortality in both countries. Currently there are few studies to compare the environmental and genetic risk factors for US and Chinese populations with regards to lung cancer incidence and mortality. The authors discuss the impact of gender and exposure risks, mainly smoking and environmental pollutants. Of high importance is the incidence of lung cancer in never smokers that is significantly higher in China than in the United States; this is particularly notable in women. These data suggest inclusion of ambient air pollution exposure and gender into lung cancer risk prognostic models to better capture high-risk individuals, especially for non-smoking women. Highlights: Recently, the lung cancer motality rate has decreased gradually in the US while it is still increasing in China. The decline in smoking prevalence and impact of clean air legislation are main contributors to the falling trend in the US. In China, the crude mortality rate is highest in more developed areas (the east coast) with highest levels of ambient fine particulate matter (PM2.5 ). Lung cancer screening impact in China may increase by including women with high exposures to PM2.5 and environmental tobacco smoke.